Ocena obrazu klinicznego, skuteczności leczenia oraz funkcji narządu wzroku u dzieci i młodzieży z toksokarozą oczną - Urban, Beata; Bakunowicz-Łazarczyk, Alina; Szumiński, Michał (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Toxocariasis is caused by Toxocara canis, the intestinal nematode commonly found in dogs. Patients are mostly young children, with an average age of 7.5 years. Patients have unilateral progressive painless vision loss and occasional leukocoria. Ocular toxocariasis has a variable presentation, from localized peripheral or macular granulomas to chronic endophthalmitis. Material and methods: Clinical features, the effectiveness of treatment and function of vision organ in 19 children and adolescents with ocular toxocariasis were analyzed retrospectively. Results: The mean patient age was 10.3 years. Inflammation was unilateral in all patients. In 11 cases (57.9%) there was peripheral granuloma, in 3 cases (15.8%) posterior pole granuloma and endophthalmitis in 5 cases (26.3%). Zentel was applied in 14 patients, Hetrazan in 3 patients and Mintezol in 2 patients. Improvement of visual acuity was achieved in 11 eyes (57.9%), no improvement in 7 eyes (36.8%), deterioration in 1 eye (5.3%). Conclusions: Ocular toxocariasis is the disease with differentiated clinical presentation. Toxocara uveitis can cause significant vision loss. In some cases quick diagnosis and effective treatment with corticosteroids and antihelminthics allowed to obtain clinical improvement.